2009
DOI: 10.1128/jb.00196-09
|View full text |Cite
|
Sign up to set email alerts
|

The StkP/PhpP Signaling Couple inStreptococcus pneumoniae: Cellular Organization and Physiological Characterization

Abstract: In Streptococcus pneumoniae, stkP and phpP, encoding the eukaryotic-type serine-threonine kinase and PP2C phosphatase, respectively, form an operon. PhpP has the features of a so-called "soluble" protein, whereas StkP protein is membrane associated. Here we provide the first genetic and physiological evidence that PhpP and StkP, with antagonist enzymatic activities, constitute a signaling couple. The StkP-PhpP couple signals competence upstream of the competence-specific histidine kinase ComD, receptor for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 51 publications
2
50
0
1
Order By: Relevance
“…S4). So far only StkP and RitR have been identified as targets of PhpP (26,27,38), but our analysis also identifies DivIVA as an in vivo target of PhpP.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…S4). So far only StkP and RitR have been identified as targets of PhpP (26,27,38), but our analysis also identifies DivIVA as an in vivo target of PhpP.…”
Section: Resultsmentioning
confidence: 86%
“…Previous work has shown that StkP acts as a dimer (25) and forms a signaling couple with its cognate phosphatase PhpP, which is a predicted cytoplasmic protein (26,27). PASTA domains of StkP were shown to bind synthetic and native PG subunits and β-lactam antibiotics (28).…”
mentioning
confidence: 99%
“…The physiological functions of eSTPs are not as well understood as those of eSTKs, and Table 2 is a comprehensive list of their identified substrates. S. pyogenes eSTP and S. pneumoniae PhpP deletion mutants are nonviable, highlighting the importance of eSTPs in bacterial physiology (72,131). However, a deletion of S. pneumoniae PhpP could be obtained when the eSTK (StkP) located in the same operon was also deleted, suggesting that an important role of these phosphatases is to modulate the autophosphorylation state of their partner kinases (131).…”
Section: Ppm Family Estpsmentioning
confidence: 97%
“…S. pyogenes eSTP and S. pneumoniae PhpP deletion mutants are nonviable, highlighting the importance of eSTPs in bacterial physiology (72,131). However, a deletion of S. pneumoniae PhpP could be obtained when the eSTK (StkP) located in the same operon was also deleted, suggesting that an important role of these phosphatases is to modulate the autophosphorylation state of their partner kinases (131). For example, autophosphorylated StkP is a substrate for PhpP (125), the kinase activity of autophosphorylated M. tuberculosis PknB is reduced by PstP-mediated dephosphorylation (18,26), B. subtilis PrpC dephosphorylates PrkC in vitro (127), the enzymatic function of the Bacillus anthracis eSTK Ba-Stk1 is reduced after desphosphorylation by the eSTP Ba-Stp1 (161), and a strong interaction was reported between the M. xanthus eSTP Pph1 and the eSTK Pkn5 (180).…”
Section: Ppm Family Estpsmentioning
confidence: 99%
“…Streptococcus sp.) also led to the notion that it may be essential (9,10,26). Recently, Agarwal et al (27) described the importance of the Stp1 homologue (SP-STP) of Group A Streptococcus (GAS) to its pathogenesis.…”
mentioning
confidence: 99%